Family Resilience: a research and intervention approach with multiproblem families - Gómez, Esteban; Kotliarenco, María Angélica (Revista de Psicología, 2010)
The concept of family resilience is presented, revising its historical antecedents, current developments and possible applications in the field of clinical, psychosocial and health intervention with highly vulnerable families. This approach allows the articulation of theoretical and empirical contributions of fields unconnected until now, such as developmental sciences, family therapy and biopsychosocial intervention with vulnerable families and children. It distinguishes between chronic risks, significant crisis or family tension, in whose presence different resilience processes are activated. Family resilience is defined as the group of processes of reorganization of meanings and behaviors, which a family under stress activates to recover and maintain optimal levels of functioning and wellbeing, balancing resources and family needs. There are a lot of methodological topics to be resolved, such as the integral evaluation of families, the need for longitudinal studies and research specially designed to be congruent with this approach.